Problematika Penerapan Kurikulum Merdeka dalam Mata Pelajaran Pendidikan Biologi di SMA Al-Hidayah Medan - Afinni, Ummi Nur; Aulia, Ayu Rizki; Wardana, Balqis Putri; Mawaddah, Hanifa; Hafizhah, Kayla Nur; Husnaa, Tsaabitah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this research is to find out the problems with implementing the independent curriculum in biology subjects at SMA Al-Hidayah Medan and also to find out what solutions educators have made in dealing with the problems they are experiencing. This research was conducted on July 12, 2023 using a qualitative approach and conducting interview sessions as well as documentation as a data collection technique. The data analysis technique is done by asking questions and writing important notes. The results of the study indicate that there are several obstacles, both internal and external factors. On the internal factor educators experience a little difficulty in planning learning activities and also managing time to convey the material to be taught. On external factors, educators experience difficulties in conveying material because each student has a different character and also the lack of infrastructure provided. Keywords: Difficulty, Educator, Character